THE WEED FLORA OF THE RECREATION AREAS OF CENTRAL DISTRICTS IN ŞANLIURFA (TÜRKIYE): The Weed Flora of of Central Districts in Şanlıurfa (Türkiye) - KAYA, OMER FARUK; ÇIÇEK, Ahmet Hamdi; TOSYAGÜLÜ ÇELİK, Hatice (Polish Journal of Natural Sciences, 2025)
The aim of this study was to determine the weed flora of recreation areas within borders of Eyyübiye, Haliliye and Karaköprü central districts of Şanlıurfa. A field study was carried out in 34 recreation areas within these districts. As a result of the study, 134 plants belonging to 27 families were identified. There were 82 were species, 31 were subspecies and 21 were varieties from these taxa. 109 of them are dicotyledonous and 25 are monocotyledonous. When evaluated in terms of life form, 1 is a phanerophyte, 1 is a chamaephyte, 30 are hemicryptophyte, 2 are cryptophyte (geophyte) and 100 are therophyte. The distribution rates according to phytogeographical regions are Irano-Turanian elements % 13 (17), Mediterranean elements % 7 (10), Euro-Siberian elements 5% (7), Eastern Mediterranean elements 4% (5) and unknown 71% (95). Considering the number of identified taxa, the first five families are Fabaceae (29), Poaceae (24), Asteraceae (23), Brassicaceace (6), Plantaginaceae (6), Apiaceae (5) and Caryophyllaceae (5).